TANTANGAN DAN PELUANG IMPLEMENTASI AI DALAM LAYANAN PUBLIK (STUDI KUALITATIF DI KOTA BANDUNG) - Ari Safrizal Wildan; Ai Nunung; Mira Veranita; Dyah Bayu Framesthi (JURNAL EKONOMI BISNIS DAN MANAJEMEN (EKO-BISMA), 2025)
Digital transformation in the government sector encourages the adoption of Artificial Intelligence (AI) technology to improve the efficiency, transparency, and accessibility of public services. Bandung City as one of the pioneers of the Smart City concept has integrated AI in various aspects of public services, such as population administration, taxation, licensing, and public complaints. However, the implementation of AI still faces various challenges, including limited infrastructure, readiness of human resources (HR), immature regulations, and low levels of public trust in the security and effectiveness of AI-based systems. This study uses a case study method with a qualitative approach to explore the effectiveness of AI implementation in Bandung City. The results show that although AI has the potential to improve bureaucratic efficiency and service quality, the level of public acceptance is still low due to the lack of digital literacy and concerns about data security. Therefore, a strategy is needed to increase digital literacy, strengthen data protection regulations, and improve technological infrastructure so that AI can be adopted more widely and effectively in public services.